Comentarios sobre la coyuntura nacional y el impacto del análisis económico del derecho en las instituciones públicas - Ghersi Silva , Enrique Alberto (2023)
On this occasion, ADVOCATUS had the pleasure of meeting with the prominent national lawyer Enrique Ghersi, specialized in the Law and Economics and co-author of the book "El otro sendero" —1986—, who kindly granted us an interview in which, starting from a broad approach that includes the Law and Economics and the Public Choice, he presented his appreciations on current issues such as corruption, the lack of political representation, university reform, among others, as well as on the contributions of the Law and Economics in public institutions.